Influential factors of continuing usage of bicycle sharing system among UUM students - Chen, Wang (2019)
With the development of the Internet economy, the concept of green environmental protection, low-carbon travel at home and abroad and the sharing of bicycles for timesharing projects is booming. The shared bicycle is characterized by convenience, environmental protection, affordable and suitable for short-distance travel. It is an important way to solve the “last mile” travel. However, with the rapid development of shared bicycles system, a series of problems have arisen. The phenomenon of random and uninterrupted parking can be seen everywhere. The damage of shared bicycles is serious. Some bicycle companies are facing bankruptcy, resulting in the user's deposit being unable to be returned. Therefore, whether users will continue to use shared bicycles is a realistic issue worth exploring. Based on the expectation confirmation theory of information system continuous use, combined with the characteristics of the sharing bicycle system, factors such as perceived usefulness, satisfaction, expectation confirmation, user commitment, habits, and external environment are included in the model to study the effect of various factors on the user's willingness to continue to use. The study conducted a questionnaire survey through online methods, and collected 128 valid sample data, and mainly used SPSS20.0 and Smart PLS 3.0 software to perform descriptive statistical analysis, reliability and validity test and correlation analysis to verify the theoretical model proposed in this study. Through empirical research, it is found that habit, perceived usefulness, external environment, user commitment, and satisfaction have a significant positive impact on the willingness of shared bicycle users to continue to use.